Investigating Agile Practices in Software Startups - Souza, Renata; Rocha, Larissa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Software development practices have smoothly shifted from traditional software development to new approaches that fit better to the real and unpredictable world. Agile practices might help practitioners respond quickly to customer change requests and deliver a working software on-schedule. Software startups are companies that develop innovative and software-intensive products and services in a dynamic and fast-growing market. This study aims to investigate the use of agile practices in software startups. We conducted 14 in-depth semi-structured interviews with the CEO and CTO from early-stage software startups. The results indicate that DevOps, Fundamentals, Design and Extreme Programming are the most used agile practice areas. Our results open up an opportunity to improve software engineering practices in early-stage software startups.